Deep Habits - RAVN, MORTEN; SCHMITT-GROHE, STEPHANIE; URIBE, MARTIN (Review of Economic Studies, 2006)
This paper generalizes the standard habit-formation model to an environment in which agents form habits over individual varieties of goods as opposed to over a composite consumption good. We refer to this preference specification as “deep habit formation”. Under deep habits, the demand function faced by individual producers depends on past sales. This feature is typically assumed ad hoc in customer-market and brand-switching-cost models. A central result of the paper is that deep habits give rise to countercyclical mark-ups, which is in line with the empirical evidence. This result is important, because ad hoc formulations of customer-market and switching-cost models have been criticized for implying procyclical and hence counterfactual mark-up movements. Under deep habits, consumption and wages respond procyclically to government-spending shocks. The paper provides econometric estimates of the parameters pertaining to the deep-habit model.